KERJA SAMA INDONESIA-BELANDA TAHUN 2019-2021 STUDI KASUS: IMPLEMENTASI MEMORANDUM OF UNDERSTANDING (MOU) JOINT PRODUCTION ON SUSTAINABLE PALM OIL - Revni Rahayu; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to explain the implementation of the Memorandum of Understanding (MoU) Joint Production on Sustainable Palm Oil between Indonesia and Netherlands during the period 2019 to 2021. This cooperation is based on the fact that the European Union is trying to block Indonesian Crude Palm Oil (CPO) into Europe. In fact, Indonesia is the world's largest exporter which has many interests in this sector. This research is a qualitative research in the form of descriptive analysis. The data collection technique used is document analysis, by collecting data in the form of secondary data. Secondary data are documents consist of books, articles, journals, press releases, and various other public records. This study uses the theory of international cooperation as an analytical tool to explain the implementation of the memorandum of understanding between Indonesia and the Netherlands. This research shows that Indonesia and the Netherlands formed the Bilateral Economic Commission as a forum for dialogue to make technical arrangements regarding the continuation of their cooperation. The National Initiatives for Sustainable and Climate Smart Oil Palm Smallholders (NI-SCOPS) is a form of support from the Dutch government for Indonesia with the aim that Indonesian oil palm farmers meet sustainability standards in their production practices, while also contributing to efforts to reduce carbon gas emissions in accordance with the spirit of improvement environment. Keyword : MoU, bilateral cooperation, crude palm oil, Joint Production on Sustainable Palm Oil